Matching-Adjusted Indirect Comparison of the Efficacy and Safety of Difamilast 1% and Delgocitinib 0.5% in Patients with Moderate-to-Severe Atopic Dermatitis - Takeshi Nakahara; Hiroyuki Murota; Miyuki Matsukawa; Hiroe Takeda; Yilong Zhang; Tomohiro Kondo (Adis, Springer Healthcare, 2024)
Abstract Background Atopic dermatitis (AD) is a chronic condition with an increasing incidence in Japan. Difamilast and delgocitinib are both new topical drugs for AD proven to be efficacious and safe in phases 2 and 3 clinical trials in Japan. However, there are no head-to-head trials comparing their efficacy and safety. The aim of this study was to determine the proportion of patients by severity and compare the clinical efficacy and safety of difamilast with delgocitinib among patients with moderate-to-severe AD using a matching-adjusted indirect comparison (MAIC). Methods Phase 3 clinical trials of difamilast and delgocitinib for treating AD were included. The trials had similar designs but differed in baseline population characteristics. Anchored MAIC was used to align the baseline characteristics and calculate clinical outcomes. The primary outcome was to determine severity stages of the proportion of patients with AD through Eczema Area and Severity Index (EASI), while the secondary outcome included comparing other clinical efficacy and safety of difamilast with delgocitinib. Results A total of 340 patients were selected (170 each received difamilast and placebo) from the difamilast trial, with 158 (106 received delgocitinib; 52 received placebo) from the delgocitinib trial for the analysis. After matching patients from the difamilast trial with those from the delgocitinib trial, the effective sample sizes (ESS) reduced to 32.7-43.3% of the original difamilast (treatment/placebo) patients. At week 4, the ESS in the difamilast group demonstrated no statistically significant differences in the distribution of AD severity stages, as per EASI scores, compared with the delgocitinib group. In addition, no significant differences were found in modified EASI (mEASI) scores, mEASI 50 and 75 scores, and safety outcomes between the two treatments. Conclusions The anchored MAIC analysis indicates that difamilast treatment, like delgocitinib, is a useful option for the treatment of patients with moderate-to-severe AD in Japan.